The Relationship of Adolescent Girl's Knowledge About the Risks of Free Sex and Safe Sex Practices - Armadison, Sonia Yustisia; Dewanti, Linda; Jayanti, Ratna Dwi; Amalia, Rize Budi (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2025)
Introduction: Free sex can negatively impact adolescent reproductive and psychological health. Knowledge of the risks of promiscuous sex is expected to raise awareness and encourage adolescents to practice safe sex. Objective: to determine the relationship between knowledge of free sex risk and safe-sex practices among adolescent girl. Methods: used an observational analytic design with a cross-sectional approach. Data were collected using an online questionnaire by google form about student’s knowledge of the risks of free sex and safe-sex practices. The sample totaled 122 adolescent girls, which were taken using the Total Sampling technique. Data analysis was conducted using the spearman test to determine the relationship between knowledge of the risks of free sex and safe-sex practices. This study has been approved by the ethics committee of the faculty of Medicine at Airlangga University. Results: Most of the respondents who have knowledge about the risks of free sex have safe sex practices, namely as many as 121 respondents (99.2%). The results of the statistical test using Spearman test requirements of the test were not met, show that the p-value in this study was 0.821 > 0.05. Knowledge of free sex risk and knowledge of safe sex did not correlate with safe sex practice. Conclusions: There was no relationship between adolescents' knowledge of the risks of free sex and safe sex knowledge and safe sex practices.